Combining high‐pressure freezing with pre‐embedding immunogold electron microscopy and tomography. (21st May 2018) - Hess, Michael W.; Vogel, Georg F.; Yordanov, Teodor E.; Witting, Barbara; Gutleben, Karin; Ebner, Hannes L.; de Araujo, Mariana E. G.; Filipek, Przemyslaw A.; Huber, Lukas A.
Abstract : Immunogold labeling of permeabilized whole‐mount cells or thin‐sectioned material is widely used for the subcellular localization of biomolecules at the high spatial resolution of electron microscopy (EM). Those approaches are well compatible with either 3‐dimensional (3D) reconstruction of organelle morphology and antigen distribution or with rapid cryofixation—but not easily with both at once. We describe here a specimen preparation and labeling protocol for animal cell cultures, which represents a novel blend of specifically adapted versions of established techniques. It combines the virtues of reliably preserved organelle ultrastructure, as trapped by rapid freezing within milliseconds followed by freeze‐substitution and specimen rehydration, with the advantages of robust labeling of intracellular constituents in 3D through means of pre‐embedding NANOGOLD‐silver immunocytochemistry. So obtained thin and semi‐thick epoxy resin sections are suitable for transmission EM imaging, as well as tomographic reconstruction and modeling of labeling patterns in the 3D cellular context. Abstract : A new approach for high‐resolution imaging of organelle morphology and associated immunogold label is presented. Rapid cryoimmobilization (HPF) and freeze‐substitution (FS), which provide quite reliable snapshots of the dynamic subcellular architecture, are successfully merged with pre‐embedding immunogold labeling (pre‐IEM). So obtained epoxy resin sections allow for standard electron microscopy, as well as electron tomographic reconstruction and modeling of cell ultrastructure and antigen distribution in 3‐dimensions (3D).